2018
DOI: 10.3390/ijms19041081
|View full text |Cite
|
Sign up to set email alerts
|

Effective Delivery of Arsenic Trioxide to HPV-Positive Cervical Cancer Cells Using Optimised Liposomes: A Size and Charge Study

Abstract: Despite the success of arsenic trioxide (ATO) in treating haematological malignancies, its potential to treat solid tumours has not been fully exploited, owing to its dose-limiting toxicity and poor pharmacokinetics. In order to overcome this hurdle, liposomal encapsulation of the drug with different surface charges (neutral, negative, and positive) and sizes (100, 200 and 400 nm) were synthesised and tested on human papilloma virus (HPV)-positive HeLa and HPV-negative HT-3 cervical cancer cell lines. Two epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…With our liposomal formulations, the highest encapsulation of carboplatin was obtained with the cationic pegylated formulation L4, which reached a concentration similar to that previously reported by Zhang et al [ 38 ]. Our results also support the hypothesis that higher drug loading can be obtained with positive liposome compared to those with a negative charge [ 39 , 40 ], which can be further increased by adding PEG [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…With our liposomal formulations, the highest encapsulation of carboplatin was obtained with the cationic pegylated formulation L4, which reached a concentration similar to that previously reported by Zhang et al [ 38 ]. Our results also support the hypothesis that higher drug loading can be obtained with positive liposome compared to those with a negative charge [ 39 , 40 ], which can be further increased by adding PEG [ 40 ].…”
Section: Discussionsupporting
confidence: 86%
“…The delivering capacity depends on the structure and composition of the nanoparticles [42,43]. In order to optimize an ATO drug nanocarrier for targeting HPV-infected cervical cells, we firstly optimised ATO encapsulating liposomes, with respect to size and charge, for use as delivery vehicles for our target cells [9]. The second parameter, targeting specificity, is mainly determined from the choice of the ligand and how it interacts with the off-target molecules and cells [20].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have indicated that HPV infection might also be responsible for a subset of anal, vulvar, vaginal, penile, upper respiratory-digestive tract, and head and neck cancers [5,6,7,8]. Therefore, targeting HPV infection has become a priority in managing HPV-associated cancers, and an anti-HPV agent that can specifically be taken up by HPV-infected cells is ideally required to enhance treatment and minimise off-target toxicity to surrounding non-HPV-infected cells and tissues [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some materials have been found to facilitate the controlled release of ATO, avoid severe toxicity and reduce side effects. 9 Sheldon 10 used ATO/magnetic nanoparticle (MZF) thermosensitive magnetoliposomes to explore the way in which inorganic arsenic inhibits cell cycle progression through the E2F1-retinoblastoma protein (pRB) as well as its application in cancer therapy. Jadhav et al 11 synthesized dimercaptosuccinic acid (DMSA)/chitosan for coating ATO nanoparticles to study their in vitro antiproliferative activity along with their mechanism of action on LNCaP and PC-3 cell lines.…”
Section: Introductionmentioning
confidence: 99%